2011
DOI: 10.1007/s10162-011-0297-9
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Modulates Auditory Function in the Hearing Cochlea

Abstract: Neurotrophins prevent spiral ganglion neuron (SGN) degeneration in animal models of ototoxin-induced deafness and may be used in the future to improve the hearing of cochlear implant patients. It is increasingly common for patients with residual hearing to undergo cochlear implantation. However, the effect of neurotrophin treatment on acoustic hearing is not known. In this study, brain-derived neurotrophic factor (BDNF) was applied to the round window membrane of adult guinea pigs for 4 weeks using a cannula a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 53 publications
2
23
2
Order By: Relevance
“…Further, this outcome is consistent with recent in vivo outcomes (Landry et al, 2011). Following combined BDNF and NT3 delivery in the deafened guinea pig model, thresholds of electrically evoked auditory brainstem responses in neurotrophin-treated animals were lowered relative to treatment with artificial perilymph (Landry et al, 2011;Sly et al, 2012). This effect was also reported with BDNF alone (Agterberg et al, 2009;Leake et al, 2011;Shepherd et al, 2005;Shinohara et al, 2002).…”
Section: Firing Threshold and Latency Are Influenced Both By Neurotrosupporting
confidence: 89%
See 3 more Smart Citations
“…Further, this outcome is consistent with recent in vivo outcomes (Landry et al, 2011). Following combined BDNF and NT3 delivery in the deafened guinea pig model, thresholds of electrically evoked auditory brainstem responses in neurotrophin-treated animals were lowered relative to treatment with artificial perilymph (Landry et al, 2011;Sly et al, 2012). This effect was also reported with BDNF alone (Agterberg et al, 2009;Leake et al, 2011;Shepherd et al, 2005;Shinohara et al, 2002).…”
Section: Firing Threshold and Latency Are Influenced Both By Neurotrosupporting
confidence: 89%
“…This effect was also reported with BDNF alone (Agterberg et al, 2009;Leake et al, 2011;Shepherd et al, 2005;Shinohara et al, 2002). Moreover, these neurotrophinmediated outcomes were not limited to the deafened system or electrical stimulation, since BDNF application in animals with normal hearing also resulted in a reduction of thresholds in the acoustically-evoked auditory brainstem response (Sly et al, 2012). Our results lend support to these previous findings by confirming that thresholds are reduced at the single neuron level in the presence of combined application of BDNF and NT3.…”
Section: Firing Threshold and Latency Are Influenced Both By Neurotrosupporting
confidence: 83%
See 2 more Smart Citations
“…To determine the functional outcomes of neurotrophin delivery, both in vivo and in vitro studies have examined the impact of BDNF and/or NT3 on neuronal activity6232425. Initial in vitro studies revealed that BDNF and NT3 had opposing effects on SGNs, and suggested that application of one or the other would propagate different firing patterns2.…”
mentioning
confidence: 99%